Development of Digital Literacy – Translanguaging and Transmedia Note Taking Formats for Academic Reading - Agnieszka Ślęzak-Świat (Theory and Practice of Second Language Acquisition, 2022)
Generative note taking, being one of the strategies applied to manage difficult texts, requires not only comprehension and selection of information but also production. The current study focuses on note taking formats for a text read with the intention to summarise. Its focal aim is to improve both practical and theoretical understanding of this activity. It involves 103 second year English Department students, investigating how readers of FL engage with complex texts, how they were instructed in note taking and what note taking strategies they employ for comprehending academic texts.